PENGARUH PERMAINAN HULA HOOP THOUSAND HAND CHAIN TERHADAP PERILAKU KERJASAMA ANAK USIA 5- 6 TAHUN DI TK IT AL-RAHBINI GONDANGLEGI KABUPATEN MALANG - Dahlia Ama Amalia; Nur Hidayah; Yudithia Dian Putra (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Cooperation skills are an essential aspect of early childhood social development that need to be optimally stimulated through meaningful and enjoyable learning activities. However, preliminary observations at TK IT Al-Rahbini Gondanglegi, Malang Regency, indicated that the cooperation skills of children aged 5–6 years had not developed optimally, as reflected in low participation in group activities and a tendency to engage in individual play. This study aimed to examine the effect of the thousand hand chain hula hoop game on the cooperative behavior of children aged 5–6 years. This research employed a quantitative approach using a simple experimental research design. The research subjects consisted of 25 children from Group B at TK IT Al-Rahbini Gondanglegi. Data were collected through structured observation of children’s cooperative behaviors, including interaction skills, role sharing, turn-taking, and helping peers. The data were analyzed using descriptive and inferential statistical techniques. The results of the study revealed that the implementation of the thousand hand chain hula hoop game had a positive effect on improving children’s cooperative behavior. Children demonstrated enhanced abilities in communication, cooperation, and completing tasks collaboratively. Therefore, the thousand hand chain hula hoop game can be considered an effective alternative learning activity for fostering cooperative behavior in early childhood education.